A revised description of the larva of Homilia leucophaea (Rambur 1842) (Trichoptera: Leptoceridae) and comparisons with the known western European Athripsodes larvae - Forcellini, Maxence; Statzner, Bernhard; Tachet, Henri (Zootaxa, 2013)
Co-occurrence of mature larvae and male pharate pupae in benthos samples from the Loire River enabled descriptions of the larva of Homilia leucophaea. Using characters of the head capsule, the labrum, the meso- and metanotum, and the pro-and metathoracic legs, we compared H. leucophaea with larvae of six western European Athripsodes species, including a larval key to these species. The larva of H. leucophaea shares characters with some of the six Athripsodes species. How-ever, without a phylogenetic analysis including larvae, pupae, and adults of Homilia species from the Afrotropical Region, it is currently impossible to decide about a potential synonymy between Athripsodes and Homilia.